2006
DOI: 10.1111/j.1365-2929.2006.02502.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical teachers as role models: perceptions of interns and residents in a Lebanese medical school

Abstract: Clinical teachers, practising in a non-occidental cultural and medical learning environment, are considered very frequently as role models by their interns and residents and have a positive impact on their professional learning and career choices. Strategies to reinforce role modelling are needed in Lebanon, in order to pass a broad spectrum of professional values to our students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 18 publications
5
53
1
4
Order By: Relevance
“…Again 34-42% of students think it should be learned through experience. Various studies although concluded that professionalism is best learned from faculty role models (Brown et al, 2009;Cruess et al, 2008;Wright et al, 1998;Paice et al, 2002;Yazigi et al, 2006;Kenny, 2003;Salam et al, 2010;Goldie et al, 2007;Cote and Leclere, 2000;Reynolds, 1994;Salam et al, 2012a) the present work is contrary as only 10-28% of students stated for role models (Table III and IV). The study respondents were very fresh students hence authors believe that they do not have enough experience about role models.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Again 34-42% of students think it should be learned through experience. Various studies although concluded that professionalism is best learned from faculty role models (Brown et al, 2009;Cruess et al, 2008;Wright et al, 1998;Paice et al, 2002;Yazigi et al, 2006;Kenny, 2003;Salam et al, 2010;Goldie et al, 2007;Cote and Leclere, 2000;Reynolds, 1994;Salam et al, 2012a) the present work is contrary as only 10-28% of students stated for role models (Table III and IV). The study respondents were very fresh students hence authors believe that they do not have enough experience about role models.…”
Section: Discussioncontrasting
confidence: 54%
“…Thus, educators play crucial role in the development of undergraduate' expertise during their course work (Salam et al, 2011a;Nabishah et al, 2009). The lectures personal charisma act as role model and has concrete influence on students for the development of professionalism (Wright et al, 1998;Paice et al, 2002;Yazigi, 2006;Kenny, 2003). This mode has long been used as unceremonious part of medical training.…”
Section: Discussionmentioning
confidence: 99%
“…Related functions were humanism and professionalism. A role model is defined by clinical excellence (15,(18)(19)(20)(21)(22)(23)(24) and humanistic personality (15,19,20,22,24), as well as effective teaching skills (21,26).…”
Section: E T Hod Smentioning
confidence: 99%
“…Clinical excellence: clinical excellence and competency (15,(18)(19)(20)(21)(22)(23)(24) are essential elements of role modeling. Clinical competency is defined as well qualified clinical practice for the diagnosis and appropriate interventions for the patient and family as well as possessing required knowledge, skills, decision making ability, clinical reasoning and effective communication skills with patients and staff (15,19,(22)(23)(24).…”
Section: E T Hod Smentioning
confidence: 99%
See 1 more Smart Citation